Piloting ASARECA’s policy manager tool through joint analysis of Uganda’s National Agricultural Extension Policy - Barungi, J.; Ssebwana, A.; Ires, Idil (International Water Management Institute (IWMI), 2024)
The Association for Strengthening Agricultural Research in Eastern and Central Africa (ASARECA) together with International Water Management Institute (IWMI) on behalf of the CGIAR initiative on Diversification in East and Southern Africa (Ukama Ustawi) organized a three-day workshop to pilot ASARECA’s policy manager tool through joint analysis of Uganda’s National Agricultural Extension Policy (NAEP) on 26-28 November 2024 at Golden Tulip Kampala Hotel, Uganda. The workshop’s objective was to pilot ASARECA’s policy manager tool. The workshop also sought to (i) discuss and familiarize with ASARECA’s policy manager tool; (ii) discuss the formulation of Uganda’s National Agricultural Extension Policy; (iii) review the implementation of Uganda’s National Agricultural Extension Policy; and (iv) analyze Uganda’s National Agricultural Extension Policy using ASARECA’s Policy Manager Tool. It was attended by 29 participants comprising 18 males and 11 females, representing key agriculture stakeholders. The workshop was facilitated through presentations, plenary discussions, and group work.